Modulation of Sn concentration in ZnO nanorod array: intensification on the conductivity and humidity sensing properties - Ismail, A. S.; Mamat, M. H.; Banu, I. B. Shameem; Malek, M. F.; Yusoff, M. M.; Mohamed, R.; Ahmad, W. R. W.; Abdullah, M. A. R.; Md. Sin, N. D.; Suriani, A. B.; Ahmad, M. K.; Rusop, M. (Springer, 2018)
Tin (Sn)-doped zinc oxide (ZnO) nanorod arrays (TZO) were synthesized onto aluminum-doped ZnO-coated glass substrate via a facile sonicated sol–gel immersion method for humidity sensor applications. These nanorod arrays were grown at different Sn concentrations ranging from 0.6 to 3 at.%. X-ray diffraction patterns showed that the deposited TZO arrays exhibited a wurtzite structure. The stress/strain condition of the ZnO film metamorphosed from tensile strain/compressive stress to compressive strain/tensile stress when the Sn concentrations increased. Results indicated that 1 at.% Sn doping of TZO, which has the lowest tensile stress of 0.14 GPa, generated the highest conductivity of 1.31 S cm− 1. In addition, 1 at.% Sn doping of TZO possessed superior sensitivity to a humidity of 3.36. These results revealed that the optimum performance of a humidity-sensing device can be obtained mainly by controlling the amount of extrinsic element in a ZnO film.